Analisis Pasal 40 Undang-Undang KPK: Dampak Penghentian Penyidikan Setelah Dua Tahun Terhadap Efektivitas Pemberantasan Korupsi - Saputri, Devita; Hartanto, Hartanto (VIVA THEMIS, 2025)
The law against corruption is one of the main priorities in Indonesia. Article 40 of Law. No. 19 of 2019 authorizes the Corruption Eradication Commission (KPK) to stop investigations that are not completed within two years by issuing a Letter of Termination of Investigation (SP3). This study aims to analyse the impact of the implementation of Article 40 on the effectiveness of corruption eradication in Indonesia. Using qualitative research methods and a descriptive-analytical approach, the results of the study show that this provision provides legal certainty, but also creates a dilemma in resolving complex corruption cases. Technical obstacles, limited resources, and the potential for misuse of regulations are significant challenges in the implementation of Article 40. This study recommends the need for policy evaluation and revision to support efforts to eradicate corruption effectively without sacrificing the principle of justice